Beyond Firm and Industry Effects on Profitability in Imperfect Markets - Scott, John T.; Pascoe, George (The Review of Economics and Statistics, 1986)
The Federal Trade Commission's Line of Business data imply that the effect of an industry's seller concentration on profitability has been misinterpreted because it has not been conditioned on capital intensity. Conclusions that market share rather than seller concentration is the primary structural determinant of profitability, and that mutual dependence recognized among oligopolistic sellers is less important than superiority effects of large-share firms, appear unwarranted. Significant firm effects exist, and explanatory power for a conventional model of structure and performance is found to be small relative to that of the general linear model within which the conventional model is nested.